Differential rates of phenotypic introgression are associated with male behavioral responses to multiple signals. (16th September 2015) - Greig, Emma I.; Baldassarre, Daniel T.; Webster, Michael S.
<x xml:space="preserve">Abstract</x> Sexual selection on multiple signals may lead to differential rates of signal introgression across hybrid zones if some signals contribute to reproductive isolation but others facilitate gene flow. Competition among males is one powerful form of sexual selection, but male behavioral responses to multiple traits have not been considered in a system where traits have introgressed differentially. Using playbacks, mounts, and a reciprocal experimental design, we tested the hypothesis that male responses to song and plumage in two subspecies of red‐backed fairy‐wren (Malurus melanocephalus) explain patterns of differential signal introgression (song has not introgressed, whereas plumage color has introgressed asymmetrically). We found that males of both subspecies discriminated symmetrically between subspecies' songs at a long range, but at a close range, we found that aggression was equal for both subspecies' plumage and songs. Taken together, our results suggest that male behavioral responses hinder the introgression of song, but allow for the observed asymmetrical introgression of plumage. Our results highlight how behavioral responses are a key component of signal evolution when recently divergent taxa come together, and how differential responses to multiple signals may lead to differential signal introgression and novel trait combinations.